2020
DOI: 10.1080/20008198.2020.1762310
|View full text |Cite
|
Sign up to set email alerts
|

The effects of PTSD treatment during pregnancy: systematic review and case study

Abstract: Background: PTSD in pregnant women is associated with adverse outcomes for mothers and their children. It is unknown whether pregnant women with PTSD, or symptoms of PTSD, can receive targeted treatment that is safe and effective. Objective: The purpose of the present paper was to assess the effectiveness and safety of treatment for (symptoms of) PTSD in pregnant women. Method: A systematic review was conducted in accordance with the PRISMA guidelines in Pubmed, Embase, PsychINFO, and Cochrane. In addition, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 47 publications
6
33
0
3
Order By: Relevance
“…Similar to previous reviews (Nillni et al., 2018; Baas et al., 2020), we found no open trials or RCTs of exposure therapies for PTSD during pregnancy. The reasons for this may be related to a fear of stressing the pregnant woman or fetus via transient increased physiological arousal, in addition to the widespread pattern of excluding pregnant women from clinical research in general (Arch et al., 2012; Blehar et al., 2013).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to previous reviews (Nillni et al., 2018; Baas et al., 2020), we found no open trials or RCTs of exposure therapies for PTSD during pregnancy. The reasons for this may be related to a fear of stressing the pregnant woman or fetus via transient increased physiological arousal, in addition to the widespread pattern of excluding pregnant women from clinical research in general (Arch et al., 2012; Blehar et al., 2013).…”
Section: Discussionsupporting
confidence: 88%
“…There is a dearth of research examining psychological interventions and treatment for PTSD symptoms among pregnant women, although the studies included in the present review provide promising avenues for further inquiry. Extending the findings of previous reviews of interventions targeting PTSD symptoms during the perinatal period (Nillni et al., 2018; Baas et al., 2020), the current review found preliminary evidence that community health workers without specialized training in mental health treatment, such as prenatal advocates in the SS intervention or “tutors” in the SMC intervention, can effectively deliver psychoeducation interventions for pregnant, trauma‐exposed women with PTSD symptoms. Psychoeducation interventions for pregnant women with PTSD symptoms may be acceptable, feasible, and associated with improved perinatal outcomes, as evidenced by studies on SS and SMC (Rowe et al., 2014; Sperlich et al., 2011; Upshur et al., 2016; Weinreb et al., 2018).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Inclusion criteria were: 1) ages 18 to 65 years; 2) a PTSD diagnosis according to the DSM-5 classification established with the Clinician-Administered PTSD Scale (CAPS-5 see below), and at least moderate severity of PTSD-symptoms (CAPS-5 score ≥26) and at least one specific memory of the traumatic event; 3) Traumata related to childhood sexual and/or physical abuse that occurred before 18 years of age, committed by a primary caretaker or an authority figure as index event; 4) sufficient fluency in Dutch to complete the treatment and research protocols. Exclusion criteria were: 1) involvement in a compensation case or legal procedures concerning admission or stay in The Netherlands; 2) pregnancy given the limited available information about safety (Baas, van Pampus, Braam, Stramrood, & de Jongh, 2020), 3) severe nonsuicidal self-injury (NSSI) which required hospitalization during the past 3 months; 4) severe suicidal behaviour: a suicide attempt during the past 3 months or acute suicidal ideations with serious intent to die with a specific plan for suicide and preparatory acts; 5) severe disorder in the use of alcohol or drugs in last 3 months according to the Mini-International Neuropsychiatric Interview (MINI; Sheehan et al, 1998), 6) cognitive impairment (estimated IQ < 70); 7) changes in psychotropic medication in the 2 months prior to inclusion; and 8) engagement in any current psychological treatment. Written informed consent was obtained from all patients after receiving a complete description of the study.…”
Section: Study Design and Participantsmentioning
confidence: 99%